Application for Recording Goods Movement on Tianjin Sunshine Plastics Co, Ltd,. - Amaliyah, Alfinatul; Setyawan, Henry Bambang; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Tianjin Sunshine Plastics Co., Ltd. (TSPC) is a manufacturing company that produces plastic. TSPC has 5 types of goods, named Jumbo Roll, Slit Roll each as much as 74 kinds with different thickness and film type, Raw Material as many as 53 kinds, Raw Recycle as much as 5 kinds and 5 kinds of Recycle which stored in multiple storage location. Recording the goods movement is still manually cause information is not integrated so that the goods movement is difficult to know, reporting the latest stock and identification of the goods takes a long time. The company needed a system for recording transactions of goods movement between storage location. The system has been built using a desktop application based on client-server. With this system every movement of goods can be recorded, inventory report and the identification of the goods can be obtained quickly and in real time so that the management can get information of stock of goods real time. From the test results and the implementation of Application for Recording Goods Movement on TSPC can be concluded that the applications created to provide recording the goods movement in an integrated manner and generate reports the latest stock information in real-time, as well as facilitate the identification of goods. Key Words: Good Movement, Stock, Real Time.